The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12890-021-01449-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ductal size on the severity of pulmonary hypertension in children with patent ductus arteriosus (PDA): a multi-center study

Abstract: Introduction Patent ductus arteriosus (PDA) is a common acyanotic heart disease that presents with variable symptoms. Objectives This study is therefore aimed at determining the relationship between gender, age, and size of PDA and pulmonary hypertension. This study also seeks to determine the prevalence of elevated pulmonary artery systolic pressure in children with PDA. Patients and methods A descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…More than 70% of the patients in both groups in our study had a mean pulmonary artery pressure > 25 mmHg, suggesting pulmonary hypertension. Thus, our study corroborates the literature [35,36] that living at a moderate altitude predisposes to a greater diameter of the ductus arteriosus and therefore a greater probability of developing pulmonary hypertension. The diameter of the PDA, however, was not the most important factor associated with the presence of hypoxia in our problem group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More than 70% of the patients in both groups in our study had a mean pulmonary artery pressure > 25 mmHg, suggesting pulmonary hypertension. Thus, our study corroborates the literature [35,36] that living at a moderate altitude predisposes to a greater diameter of the ductus arteriosus and therefore a greater probability of developing pulmonary hypertension. The diameter of the PDA, however, was not the most important factor associated with the presence of hypoxia in our problem group.…”
Section: Discussionsupporting
confidence: 92%
“…Blood hyperviscosity, thrombosis and decreased pulmonary microcirculation, as well as endothelial injury and inflammation trigger the process of remodeling and interstitial fibrosis in the alveoli capillary unit in a medium-to long-term period of time. In hemodynamic terms, this factor produces a progressive increase in pulmonary vascular resistance and the consequent development of chronic thromboembolic disease as well as secondary pulmonary arterial hypertension [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found the DA size on postnatal Day 7 significantly correlated with the risk of PH in extremely preterm infants. Although there is limited research directly assessing the association between DA parameters and PH in neonates, our findings are in line with a recent multicenter study conducted among children aged 1 month to 14 years, which reported that the prevalence of PH in children with PDA was approximately 60%, and that ductus size was positively correlated with pulmonary artery systolic pressure 22 . Additionally, previous studies have shown that PDA requiring ligation is associated with PH in preterm infants, 14,23 which partly supports our findings since a PDA requiring ligation is usually associated with a larger diameter 24,25 .…”
Section: Discussionsupporting
confidence: 91%
“…assessing the association between DA parameters and PH in neonates, our findings are in line with a recent multicenter study conducted among children aged 1 month to 14 years, which reported that the prevalence of PH in children with PDA was approximately 60%, and that ductus size was positively correlated with pulmonary artery systolic pressure. 22 Additionally, previous studies have shown that PDA requiring ligation is associated with PH in preterm infants, 14,23 which partly supports our findings since a PDA requiring ligation is usually associated with a larger diameter. 24,25 Recently, a case-control study in extremely preterm infants found that both presence of PDA and persistence of moderate to large PDA over 4 weeks after postnatal Day 28 were related to an increase of BPD-PH at discharge.…”
Section: Discussionsupporting
confidence: 89%
“…[ 1 ] It is one of the most commonly diagnosed birth defects in pre-term infants, and it is associated with mortality and potentially harmful long-term outcomes. [ 2 ] The adverse effects of an untreated PDA include: late congestive heart failure with ventricular hypertrophy; pulmonary vascular obstructive disease including Eisenmenger syndrome with shunt flow reversal, cognitive and developmental delay, infective endocarditis, aneurysmal dilatation of the ductus; and ductal calcification [ 3 ] Uncertainty remains as to when or if PDA should be treated. [ 4 , 5 ] Prophylactic and symptom-based treatments with medication, catheterization, and surgical ligation have emerged over the past decades, but these treatment strategies have yet to be proven effective.…”
Section: Introductionmentioning
confidence: 99%